Integrated load optimization of elastic‐plastic axisymmetric plates at shakedown - Venskus, Artūras; Kalanta, Stanislovas; Atkočiūnas, Juozas; Ulitinas, Tomas (Journal of Civil Engineering and Management, 2010)
An elastic‐plastic axisymmetric steel bending plate subjected to a repeated variable load (RVL) is considered. The solution to the load optimization problem at shakedown is complicated because the stress‐strain state of the dissipative systems (e.g. the plate plastic deforming) depends on their loading history. A new algorithm for the load optimization problem combining von Mises and Tresca yield criterion based on the Rosen project gradient method is proposed. The optimization results are obtained by integrating the existing software and that created by the authors.